Y Y Domination in Bipartite Graphs - Venkatakrishnan, Y.B.; Swaminathan, V. (Journal of Informatics and Mathematical Sciences, 2012)
Let G be a bipartite graph. A subset S of X is called a Y Y dominating set if S is a Y-dominating set and X-S is not a Y-dominating set. A subset S of X is called a minimal Y Y dominating set if any proper subset of S is not a Y Y dominating set. The minimum cardinality of a minimal Y Y dominating set is called the Y Y domination number of G and is denoted by γ_Y Y (G). In this paper some results on Y Y domination number are obtained.